2016
DOI: 10.1055/s-0036-1582119
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Inferior Vena Cava Filters: Technical Considerations

Abstract: Placement of retrievable inferior vena cava filters has seen rapid growth since their introduction into clinical practice. When retrieved, these devices offer the notional benefit of temporary protection from pulmonary embolism related to lower extremity deep venous thrombosis, and mitigation of filter-related deep venous thrombosis. When promptly removed after the indication for mechanical prophylaxis is no longer present, standard endovascular retrieval techniques are frequently successful. However, the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Intravascular use of endoscopic forceps has been previously described to facilitate retrieval of inferior vena cava filters and intravascular foreign bodies. 7 To our knowledge, this case report represents the first description of a novel intravascular use of endovascular forceps.…”
Section: Discussionmentioning
confidence: 81%
“…Intravascular use of endoscopic forceps has been previously described to facilitate retrieval of inferior vena cava filters and intravascular foreign bodies. 7 To our knowledge, this case report represents the first description of a novel intravascular use of endovascular forceps.…”
Section: Discussionmentioning
confidence: 81%
“…With this new type of device came an increase in the number of filters being placed; however, a lack of emphasis on filter retrieval led to an increase in the reports of complications, with complications being directly associated with filter retrieval and the length of time the filter was present 10 11. This led to the FDA recommending in 2014 that all retrievable IVC filters should be removed as soon as possible after no longer needed for protection and questioning the overall use and safety of IVC 12. However, there was compelling evidence showing them to have significant protection against pulmonary embolisms; in regards to filter removal, the benefits of placing an IVC filter seem to outweigh the risk of complications associated with the retrieval 10.…”
Section: Discussionmentioning
confidence: 99%
“…2) Although designed to be removed, the majority of filters are left in place for a prolonged period of time, and studies have demonstrated that a prolonged indwelling time results in device-related complications. 3) In this study, we report a case of IVC filter-induced thrombosis. A second filter was inserted prior to catheter-directed thrombolysis (CDT), and both filters were successfully removed 70 and 1858 days post placement.…”
Section: Introductionmentioning
confidence: 93%